Examination of Security Features in Nepali Currency of Denomination Rs. 500 and Rs. 1000 Using Video Spectral Comparator-6000 - Giri, R.; Bhattarai, P.; Chimouriya, S. P.; Ghimire, B. R. (Journal of Nepal Physical Society, 2021)
In this work, we have studied security features of Nepali currencies of denomination Rs. 500 and Rs. 1000 of recent two series with the help of Video Spectral Comparator-6000. During examination, mostly ultraviolet, normal, transmitted and oblique light are used. We found nine different security features like fluorescence, water mark, micro text, security thread, intaglio print, see through registor, emboss, optically variable ink and latent image in this work. One feature, latent image is found to be completely removed in new series of both Rs. 500 and Rs. 1000 whereas new important security feature optically variable ink is introduced in new series of Rs. 500. Besides these two features, some are unchanged while some are modified.